Kandungan Senyawa Polifenol dan Aktivitas Antioksidan Daun Tumbuhan Apu-apu (Pistia stratiotes) dengan Metode Pengeringan yang Berbeda: Polyphenol Compounds and Antioxidant activity of Water Lettuce (Pistia stratiotes) Leaf Extract with Different Drying Methods - Sabri Sudirman; Erina Aprilia; Miftahul Janna (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Increased free radicals cause damage to cells and tissues in the body. This is due to the lack of antioxidant ability in the body, therefore it requires external antioxidants. One of the plants that can be used as a source of antioxidants is water lettuce (Pistia stratiotes) because it has polyphenol compounds. However, polyphenolic compounds are thermolabile, so the drying process is important in preparation and extraction. Thus, this study aimed to extract polyphenolic compounds from the leaves of the water lettuce (P. stratiotes) with different drying methods and to determine the antioxidant activity of these compounds. Drying was carried out by 3 different methods, namely sun drying, oven at 40ºC, and freeze drying and repeated 3 times. The data were analyzed using a one-way analysis of variance (ANOVA) with Duncan's post-hoc test and presented in graphical form. The results showed the highest extraction yield on freeze-drying (15.64±1.19%) and the lowest on sun-drying (8.48±3.34%). Total polyphenols and flavonoids were also highest ​​in the freeze-drying method (32.94±1.34 mg GAE/g dry sample and 146.80±5.29 mg QE/g dry sample, respectively), while the lowest was in sun-drying. Whereas the antioxidant activity of freeze-drying (IC50 266.33±5.77 mg/mL) and oven (IC50 305.67±22.85 mg/mL) had not significantly different. However, these activities were more effective in inhibiting free radicals when compared with sun-drying (IC50 462.67±56.52 mg/mL). Therefore, freeze-drying and oven-drying can be an option as an appropriate drying method to extract polyphenol and flavonoid compounds which are used as antioxidants.